miRNA-26b Overexpression in Ulcerative Colitis-associated Carcinogenesis - Benderska, Natalya; Dittrich, Anna-Lena; Knaup, Sabine; Rau, Tilman; Neufert, Clemens; Wach, Sven; Fahlbusch, Fabian B.; Rauh, Manfred; Wirtz, Ralph M.; Agaimy, Abbas; Srinivasan, Swetha; Mahadevan, Vijayalakshmi; et al. (Inflammatory Bowel Diseases, 2015)
Longstanding ulcerative colitis (UC) bears a high risk for development of UC-associated colorectal carcinoma (UCC). The inflammatory microenvironment influences microRNA expression, which in turn deregulates target gene expression. microRNA-26b (miR-26b) was shown to be instrumental in normal tissue growth and differentiation. Thus, we aimed to investigate the impact of miR-26b in inflammation-associated colorectal carcinogenesis.Two different cohorts of patients were investigated. In the retrospective group, a tissue microarray with 38 samples from 17 UC/UCC patients was used for miR-26b in situ hybridization and quantitative reverse transcription polymerase chain reaction analyses. In the prospective group, we investigated miR-26b expression in 25 fresh-frozen colon biopsies and corresponding serum samples of 6 UC and 15 non-UC patients, respectively. In silico analysis, Ago2-RNA immunoprecipitation, luciferase reporter assay, quantitative reverse transcription polymerase chain reaction examination, and miR-26b mimic overexpression were employed for target validation.miR-26b expression was shown to be upregulated with disease progression in tissues and serum of UC and UCC patients. Using miR-26b and Ki-67 expression levels, an UCC was predicted with high accuracy. We identified 4 novel miR-26b targets (DIP1, MDM2, CREBBP, BRCA1). Among them, the downregulation of the E3 ubiquitin ligase DIP1 was closely related to death-associated protein kinase stabilization along the normal mucosa-UC-UCC sequence. In silico functional pathway analysis revealed that the common cellular pathways affected by miR-26b are highly related to cancerogenesis and the development of gastrointestinal diseases.We suggest that miR-26b could serve as a biomarker for inflammation-associated processes in the gastrointestinal system. Because miR-26b expression is downregulated in sporadic colon cancer, it could discriminate between UCC and the sporadic cancer type.
EVALuna2:1970